Application of Integration Model in Education Plan for Learning Recovery - Liza Ghazali, Puspa; Hazimi Mohammed Foziah, Nik; Firdause Md Fadzil, Ahmad; Afthanorhan, Asyraf; Mamat, Mustafa; Omar, Lazim; Shukri Yazid, Ahmad; Ansyari Guci, Dede; Rashid, Norfadzilah (International Journal of Engineering and Technology, 2018)
Islamic insurance or takaful is commonly used by the people nowadays especially in most of the Muslim countries since it has been introduced. Many studies have done to propose an efficient of the takaful application system. However, the existing models of takaful do not provide plan for the learning disabled children, even though their number is keep increasing over the years. The learning disabled children can recover with a consistent guidance and it may become a burden for the country, parents and special education teachers if something is not done to help them. Hence, they need a special plan in takaful in recovery. This study discussed on the takaful education plan for the learning disabled children which will contribute much on their learning process of recovery. Using an integrated model of takaful education plan, a new recovery model of takaful education plan is proposed which consists plan that may assists the special education teachers in educating the learning disabled children.Â Â Â